KEKUATAN MUSCULUS ABDOMINALIS DAN KELENTUKAN PINGGANG BERHUBUNGAN DENGAN KEMAMPUAN HEADING PEMAIN SEKOLAH SEPAKBOLA - M Ridwan; Afrizal S; Vega Soniawan (Jurnal Sporta Saintika, 2020)
The problem of this study is the lack of the ability to master the heading technique due to the players non optimal physical condition. Therefore, this study aims at finding the connection between the musculus abdominalis strength and the waist flexibility toward the ball heading of SBB Balai Baru players. This study used correlation research which used 119 SBB Balai Baru players as the population. The sampling technique was purposive sampling with 30 U-16 players as the participants. The instruments used for data collection were sit up test, extension dynamometer, and heading test. The data were analyzed using the analysis requirement test with normality test (lilliefors test), correlation test, and multiple correlation test. The result research indicates that there was a significant connection between (1) abdominal muscles strength and the heading ability with 0,803 correlation coefficient result, (2) the waist flexibility toward heading ability with 0,402 correlation coefficient result, and (3) the musculus abdominalis strength and the flexibility to each other toward heading ability with 0.832 multiple correlation test result. Thus, the players are expected to increase the musculus abdominalis strength and the waist flexibility to support the ball heading ability